2020
DOI: 10.1088/1742-6596/1567/3/032061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chitosan on Sperm Quality of Lead Acetate-Induced Rats

Abstract: Escalation in blood lead level may decrease sperm quality. Chelating agent, such as chitosan, is known to reduce the detrimental effects from lead exposure. This research aims to analyze the effect of chitosan on sperm quality of lead acetate-induced rats. 30 rats were divided into six groups. All treatment groups, aside from control group, were induced by 175 mg/kg weight of lead acetate. Positive control group was treated with Ca2EDTA, while negative control group was only treated with lead acetate. Treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Owing to its unique physical and chemical properties, chitosan gained more interest and was integrated into a wide range of applications in the medical field as an antibacterial agent, a drug carrier, and wound healing 11 . Chitosan improves the sperm quality of lead acetate-intoxicated rats 12 .…”
mentioning
confidence: 99%
“…Owing to its unique physical and chemical properties, chitosan gained more interest and was integrated into a wide range of applications in the medical field as an antibacterial agent, a drug carrier, and wound healing 11 . Chitosan improves the sperm quality of lead acetate-intoxicated rats 12 .…”
mentioning
confidence: 99%
“…In this respect, we determined the antioxidative action of CTZ on the oxidative stress marker (MDA), then on sperm quality that may occur via protecting the testis and preserving the sperm quality. It was reported that Chitosan restored the decrease in testicular weight with the increased incidence of sperm abnormalities (abnormal sperm morphology) and the decrease in the number of spermatozoa caused by leadtoxicity (Marianti et al, 2019). Therefore, chitosan, which is also nontoxic, has the potential for further development as alternative natural compound to overcome the negative effects to lead exposure.…”
Section: Results and Discussion Sperm Productionmentioning
confidence: 99%
“…Chitosan can enhance the size of the antral follicle, the number of endometrial arterioles, and the endometrial thickness of female rats exposed to lead acetate (Purwitasari et al, 2019). Although mammals do not have endogenous chitin (Ohno et al, 2013), a previous study demonstrated that chitosan, a derivative of a natural carbohydrate biopolymer derived from chitin deacetylation, could improve sperm count and the motility of progressive sperm of lead-acetate-induced rats (Marianti et al, 2020). This suggests that chitin and/or chitosan may be involved in the male reproductive system.…”
Section: Introductionmentioning
confidence: 99%